Ethiopia's new cybercrime legislation: Some reflections - Yilma, Kinfe Micheal (The computer law and security report, 2017)
Ethiopia has been enacting various pieces of legislation to regulate some aspects of the digital environment. The cybercrime proclamation of 2016 is the most recent addition to the statute book that criminalizes a range of cybercrimes. It has also introduced a number of novel evidentiary and procedural rules that will assist in the investigation and prosecution of cybercrimes. The law has, however, attracted criticisms from various corners mainly owing to some of its human rights unfriendly provisions. This comment provides brief analysis of the cybercrime legislation and highlights some of the challenges that lie ahead in the course of putting the law into practice.